Breast cancer and ovulation induction - Bıldırcın, Fatma Devran; Özdemir, Ayşe; Karlı, Pervin; Çetinkaya, Mehmet Bilge (Journal of Surgery and Medicine, 2019)
Breast cancer is the most common malignancy of women at reproductive age. Nowadays, with increasing early diagnosis, survival rate is higher, which is why the number of patients wanting to get pregnant are on the rise. Fertility preservation, ovulation induction, the safety of these interventions and pregnancy results are discussed in this review.